A programmable ternary CPU using hybrid CMOS/memristor circuits. Issue 4 (4th July 2018) - Wust, Daniel; Fey, Dietmar; Knödtel, Johannes
Abstract: The carry propagation of arithmetic operations is one of the major shortcomings of common binary number encodings as the two's complement. Signed-digit arithmetic allows the addition of two numbers without carry propagation and in asymptotically constant time in dependence of the word length, while at the same time requiring a digit representation with more than two states. With the advent of memristors, it has become possible to store multiple states within a single memory cell. This paper proposes an implementation of a general purpose CPU using signed-digit arithmetic by exploiting memristors in order to implement multi-value registers. The proposed model of the CPU is evaluated by the execution of various image processing algorithms. It is shown that a break-even point exists at which signed-digit algorithms outperform conventional binary arithmetic operations. Furthermore, simulation results prove that the memristor device lends itself to store signed-digit data efficiently. Graphical Abstract: Measurement of memristors behavior to store multiple discrete values. Below 5 k the digit 1 is coded, between 5 and 12.5 k the digit 0, and above 12.5 k the digit 1.